Community Based Pasung Release on Schizophrenia - Titik Dyah Agustini; Azimatul Karimah; Ivana Sajogo (Faculty of Medicine, Universitas Airlangga, 2021)
Schizophrenia is a severe mental disorder, persistent, chronic, easy to relapse. Schizophrenics at risk of becoming victims of pasung. Confinement is any form of limitation of movement of people with mental illness by families and/or communities. The government has launched the program to end pasung, but the incidence of pasung in the community is still quite high. Liberation of community-based pasung includes prevention of pasung, handling of pasung and rehabilitation of post-pasung. The method of community-based pasung release at the rehabilitation stage that is widely used is Assertive Community Treatment (ACT) and has been proven to reduce recurrence and hospitalization rates in schizophrenics so as to reduce the incidence of pasung and prevent re-pasung.